Genetic polymorphism of Plasmodium falciparum circumsporozoite protein on Bioko Island, Equatorial Guinea and global comparative analysis - Hui-Ying Huang; Xue-Yan Liang; Li-Yun Lin; Jiang-Tao Chen; Carlos Salas Ehapo; Urbano Monsuy Eyi; Jian Li; Ting-Ting Jiang; Yu-Zhong Zheng; Guang-Cai Zha; Dong-De Xie; Jin-Quan He; et al. (Malaria Journal, 2020)
Abstract Background Plasmodium falciparum circumsporozoite protein (PfCSP) is a potential malaria vaccine candidate, but various polymorphisms of the pfcsp gene among global P. falciparum population become the major barrier to the effectiveness of vaccines. This study aimed to investigate the genetic polymorphisms and natural selection of pfcsp in Bioko and the comparison among global P. falciparum population. Methods From January 2011 to December 2018, 148 blood samples were collected from P. falciparum infected Bioko patients and 96 monoclonal sequences of them were successfully acquired and analysed with 2200 global pfcsp sequences mined from MalariaGEN Pf3k Database and NCBI. Results In Bioko, the N-terminus of pfcsp showed limited genetic variations and the numbers of repetitive sequences (NANP/NVDP) were mainly found as 40 (35%) and 41 (34%) in central region. Most polymorphic characters were found in Th2R/Th3R region, where natural selection (p > 0.05) and recombination occurred. The overall pattern of Bioko pfcsp gene had no obvious deviation from African mainland pfcsp (Fst = 0.00878, p < 0.05). The comparative analysis of Bioko and global pfcsp displayed the various mutation patterns and obvious geographic differentiation among populations from four continents (p < 0.05). The global pfcsp C-terminal sequences were clustered into 138 different haplotypes (H_1 to H_138). Only 3.35% of sequences matched 3D7 strain haplotype (H_1). Conclusions The genetic polymorphism phenomena of pfcsp were found universal in Bioko and global isolates and the majority mutations located at T cell epitopes. Global genetic polymorphism and geographical characteristics were recommended to be considered for future improvement of malaria vaccine design.